Komparasi Risiko Produksi Usahatani Padi Sawah Tadah Hujan Di Daerah Dataran Tinggi Dan Rendah Di Kecamatan Balocci Kabupaten Pangkep - Fitriani; Mohammad Anwar Sadat; Arifin Arifin (Universitas Muslim Maros, 2025)
Production risk is something that cannot be avoided, especially in the agricultural sector. Because all forms of business are bound to experience risk or uncertainty, resulting in losses, this research aims to determine the risk of rainfed lowland rice production in the highlands and lowlands, to find out the comparison of production risks in highland and lowland rainfed rice farming in Balocci District, Pangkep Regency. The population in this study were farmers who cultivate rain-fed rice. The number of respondents was 74 people using a simple random method. This research uses quantitative descriptive analysis methods. Data analysis uses the method of calculating the coefficient of variation and standard deviation values.